Extra-cranial aneurysm of the internal carotid artery treated by proximal ligation. Issue 639 (January 1979) - Haywood, I. R.; Ellis, H.
Abstract : A case of aneurysm of the extra-cranial section of the internal carotid artery extending to the base of the skull is described. Treatment comprised proximal vessel ligation, the tolerance of the patient's cerebral circulation to this procedure first being assessed by measuring the back pressure across the circle of Willis after temporary carotid artery occlusion. The value of this technique is discussed.